Filter Bubbles, Echo Chambers and Shared Experience: Dewey’s Conception of the Public in the Digital Age - Weydner-Volkmann, Sebastian (Ruch Filozoficzny, 2023)
This article explores what John Dewey’s political philosophy can offer in regard to the current crisis in digital democracy. It focuses on two digital mechanisms, the “filter bubble” and the “echo chamber”. While there is a prominent, Dewey-inspired debate on “digital publics” in the literature, a reconstruction of the Deweyan concepts of the public and of shared experience shows that it does not adequately reflect the aspect of situated and embodied experience. Based on this, it is shown that digital media offerings must also be rooted in local contexts of experience in order to answer the challenge of those two problematic mechanisms.